Pelatihan teknis penentuan matang panen kelapa sawit untuk Mahasiswa - Efi said Ali; Nasution, Asmara Sari; Ani, Nurma; Ahmad, Hafiz (LPPM Universitas Al-Azhar medan, 2025)
The technical training on determining the ripeness of oil palm fruit aims to enhance the knowledge and skills of students in the field of agriculture, particularly in the management of oil palm crops. The training focuses on teaching the correct techniques for determining the optimal harvesting time to improve production efficiency, ensuring higher quality oil and reducing production losses (losses) typically associated with improper harvesting. This study presents a novel approach by combining theoretical learning on ripeness criteria with hands-on practice in the field. This approach allows students to gain practical experience in oil palm fruit harvesting, using appropriate tools such as egrek, chisel, and others. Unlike traditional training methods that mainly focus on theory, this study involves active participation in fieldwork, providing a comprehensive learning experience. The methodology employed in this community service project combines theoretical lectures and direct field practice. The training begins with lectures on the introduction to oil palm, the botany of the plant, ripeness criteria, and harvesting techniques. Afterward, participants engage in hands-on practice in the field to apply the knowledge of ripeness criteria and harvesting techniques. The harvesting process is then evaluated based on two main factors: production losses and the quality of harvested palm fruit, including oil yield and oil quality. The training proved to be effective in enhancing participants' understanding of the correct ripeness criteria and harvesting techniques, leading to a significant reduction in production losses and an increase in oil quality and yield. Evaluation results indicated a 30% reduction in production losses after implementing the techniques learned in the training. Furthermore, oil extracted from fruits harvested at the ideal ripeness stage showed the highest yield and quality. This training provides a significant contribution to improving the sustainability and productivity of the palm oil industry in Indonesia by enhancing the skills of students and workers in the industry, which ultimately benefits both the economy and the global palm oil market.